Marvel-verse. Shang-Chi. - Van Lente, Fred (Marvel Worldwide, Inc, 2021)
A collection of graphic novel stories featuring martial artist Shang-Chi, who joins his friends Wolverine and Spider-Man, and battles enemies such as Sabretooth, Midnight, the Hand, and Lady Deathstrike.